1980
DOI: 10.1111/j.1532-5415.1980.tb01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward the Geriatric Patient Among Family Practice Residents†

Abstract: For the Family Practitioner, elderly patients are a highly significant group. In the past, some health professionals have expressed negative attitudes toward the elderly. Thus a need exists to study specific factors that may influence a Family Practice resident's willingness to treat older patients. A Likert-type questionnaire was developed that utilized the Thurstone-Likert discrimination technique. Five categories were chosen for study: general attitudes, cost effectiveness, time and energy, therapeutic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 9 publications
5
66
0
Order By: Relevance
“…GPs were asked to complete a questionnaire on their baseline personal and practice characteristics, on their attitudes towards geriatric patients (Maxwell and Sullivan, 1980) and their confidence in their own abilities in diagnosis and management of dementia (Robinson et al, 2001).…”
Section: Data Collection General Practitioners (Gp)mentioning
confidence: 99%
“…GPs were asked to complete a questionnaire on their baseline personal and practice characteristics, on their attitudes towards geriatric patients (Maxwell and Sullivan, 1980) and their confidence in their own abilities in diagnosis and management of dementia (Robinson et al, 2001).…”
Section: Data Collection General Practitioners (Gp)mentioning
confidence: 99%
“…These instruments include Reuben et al's (1998) Geriatric Attitude Survey (GAS), which consists of 14 items scored on a 1-5 Likert-type (Agreement) scale; the Maxwell-Sullivan Attitude Survey (MSAS), a 28-item attitude measurement scale (Maxwell & Sullivan, 1980); and Rosencranz's factor analysis of attitudes toward the aged (Rosencranz & McNevin, 1969). Stewart et al (2006) reported reliability problems with both Reuben's GAS survey and with Maxwell-Sullivan's MASA survey; this suggests cautious use of these two instruments.…”
mentioning
confidence: 99%
“…Higher scores indicated a more negative attitude towards the elderly. 2. attitudes of GPs towards geriatric patients (Maxwell & Sullivan, 1980). The scores ranged from 28-140.…”
Section: Methodsmentioning
confidence: 99%